PENGARUH NILAI-NILAI SOSIAL DAN LINGKUNGAN KERJA TERHADAP PEMILIHAN KARIR MAHASISWA AKUNTANSI SEBAGAI AKUNTAN PUBLIK - Pratiwi, Adelia Anggi (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2021)
ABSTRAKThis study aims to determine the effect of social values and work environment on career choice as a public accountant. This research was conducted based on the current phenomenon, namely the very small growth in the number of public accountants each year, while the number of accounting graduates continues to increase every year. The method used in the sample selection is purposive sampling. Data collection techniques in this study by distributing questionnaires distributed to 94 respondents. The analytical method used in this study is multiple linear regression analysis with the help of IBM SPSS Statistics 25. The results of this study state that: (1) Social Values affect the Career Selection of Accounting Students as Public Accountants (2). Work Environment affects the Selection Career of Accounting Students as Public Accountants. Keywords: Social Values, Work Environment, Career Selection, Public Accountant REFERENSI Arnita, V. (2018). Pengaruh Orangtua Terhadap Mahasiswa Akuntansi Dalam Pemilihan Karir Menjadi Profesi Akuntan. Jurnal Akuntansi Dan Bisnis